A preliminary analysis modeling of the relationship between quality management practices and sustainable performance. Issue 1 (2nd January 2020) - Akanmu, Muslim Diekola; Hassan, Mohamad Ghozali; Bahaudin, Ahmad Yusni Bin
Abstract: From the past literature, the relationship between quality practices and sustainable performance has not adequately been explored. Hence, this research attempted to further investigate the impacts of other variables that may proffer better explanation to the nature of the relationship. Therefore, the aim of this study is to examine the mediating and moderating effect of organizational excellence and environmental regulation and policy (ERP) on the relationship between TQM (quality practices) and sustainable performance by proposing an inclusive research model comprising the antecedent factors in food and beverage industry of Malaysia. Questionnaires were distributed to 303 Malaysian food and beverages companies while 168 questionnaires were returned (response rate above 50%) and PLS-SEM was used to analyze the data in order to assess the validity and reliability of the instrument. This study serves as a validation process for the developed instruments of the research with the identified constructs of the study while the preliminary analysis and results are shown. Also, the result reveals that the instruments are reliable and the analysis indicates a strong evidence of rational validity. Similarly, it reaffirms the importance of excellence for any successful strategic implementation in enhancing sustainable performance through the implementation of quality practices.